PKBM Pelita Riau Communication Planning in Improving Positive Image of Nonformal Education - Sri Ayu Agustina (CV. INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: Nonformal education institutions, particularly Pusat Kegiatan Belajar Masyarakat (PKBM), face persistent challenges in public perception due to negative stereotypes, inadequate governmental support, and limited infrastructure. PKBM Pelita Riau, located in Pekanbaru, Riau Province, Indonesia, represents a case study in how strategic communication planning can address these image deficits and enhance the positive standing of nonformal education in the community. This study aimed to describe and analyze the communication planning process employed by PKBM Pelita Riau in improving its positive image, encompassing five key stages: research, planning, execution, measurement/evaluation, and reporting. Materials and methods: A qualitative descriptive approach was adopted. Data were collected through in-depth interviews, observation, and documentation involving the head of PKBM Pelita Riau, active tutors for Packages A, B, and C, and community members. Data validity was ensured through triangulation techniques, and analysis followed data reduction and conclusion-drawing procedures. Results: Findings revealed a five-stage communication planning framework at PKBM Pelita Riau: (1) Problem identification including negative community perceptions and low government participation; (2) Strategic planning with socialization activities such as mobile reading gardens and educational film screenings; (3) Execution through both direct and media-based community communication; (4) Evaluation to minimize identified problems; and (5) Reporting as a basis for future program development. Conclusions: PKBM Pelita Riau demonstrates that structured, multi-stage communication planning can meaningfully improve community perception of nonformal education. However, sustained improvement requires increased governmental participation and resource allocation.